Giant right atrial mass obliterating the right atrium - Ahmad Al-Fakhouri; Inyong Hwang; Shadwan F. Alsafwah (Greater Baltimore Medical Center, 2015)
A73-year-old man with past medical history of mechanical aortic valve replacement, metastatic melanoma of unknown primaries with liver metastasis, presented with progressive shortness of breath and dyspnea on exertion. Transthoracic echocardiography (TTE) showed a large homogenous mass completely occupying the right atrial cavity and extending to and nearly obstructing the inflow area of the tricuspid valve. He was treated with chemotherapy.